ROLE OF METHODS AND TOOLS IN FORMING LIBRARY SKILLS IN SOCIETY - Kadyrov Hasanboy Oribjonvich (Western European Studies, 2024)
This article reveals the need to form reading skills in the family, which is the basis of human development and the book, which is the foundation of society. The role of the book in the society is based on the pedagogical aspectsthat the formation of educated and intellectual young people is the basis of development.
Keywords: family; reading; reading culture; development